Instagram Use and Equity in Public Healt: A Study on Brazil and Portugal During t e COVID-19 Pandemic - Pinto, Pâmela; Antunes, Maria João; Almeida, Ana Margarida; Renó, Denis [UNESP] (University of Toronto Press, 2023)
Background: There are few stud es on the use of Instagram dur ng the COVID-19 pandem c n low- ncome countr es, even though Instagram s cons dered a tool to f ght COVID-19. Analysis: Th s work appl es both an exploratory approach and content analys s to study the Instagram prof les of Portugal’s Nat onal Health Serv ce and Braz l’s M n stry of Health, as well as of c t zens of these two countr es, dur ng the COVID-19 pandem c. 1,633 posts from these health author t es were analyzed. In add t on, netnography methodology was appl ed to the analys s of a total of 48,691 posts. Conclusions: C t zens and san tary author t es used Instagram as a space to d scuss the pandem c. C t zens emphas zed feel ngs and op n ons through photos. For the r part, author t es adopted the platform as an off c al commun cat on channel, w th l m tat ons regard ng the equ ty of the r content.
Keywords: COVID-19; Instagram; nst tut onal commun cat on; r sk commun cat on; soc al med a